URGENSI KOMUNIKASI DALAM KELOMPOK KECIL UNTUK MEMPERCEPAT PROSES ADOPSI TEKNOLOGI PERTANIAN (Forum Penelitian Agro Ekonomi, 2024)
Adoption process of effective agricultural technology innovation requires various forms and channels of communication between users. Personal communication between individuals and communication in small groups (farmers’ group) are two forms of communication that has been used as a mainstay in agricultural extension activities. Personal communication usually occurs horizontally between farmers, and vertically between farmers and agricultural extension officers. Personal communication between farmers can take place outside and also within farmers’ groups. This paper is a review of various theories and research results regarding the importance of communication in small groups. The results showed that communication in small groups becomes an important component in delivering information materials, i.e. technology and other information. In the group, in addition to ongoing communication, it is also a place of performing discussion and learning among peasants, as well as a unit of decision for unity of action in adopting technology.
Keywords: innovation adoption; small group; small group communication; farmer group